Synthesis and Characterization of Nanocrystalline Micro-Mesoporous ZSM-5/MCM-41 Composite Zeolite - Majeed, Najwa Saber; Saleh, Asir Abduljabbar (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Nanocrystalline micro-mesoporous ZSM/MCM-41 composite was synthesized using alkaline treatment method and two step of crystallization in poly tetraflouroethylene (PTFE) lined autoclave. The synthesized zeolites was characterized by X-Ray diffraction (XRD), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), Atomic force microscopy (AFM), Fourier transport infrared (FTIR), and N2 adsorption-desorption (BET). It was approved that the best results for alkaline leaching can be got with 1.5M NaOH solution. High surface (BET) area of 630 m2/g with pore volume of 0.55 cm3/g has been got. AFM reports showed a nano-level size for average particle size of 50nm.